Anticipated Devaluations, Currency Flight, and Direct Trade Controls in a Monetary Economy - Feenstra, Robert C. (American Economic Review, 2016)
mendation for a country facing a balance of payments deficit, this advice is often resisted by country governments. Instead, direct trade controls such as tariffs, quotas, and subsidies are frequently used. In this paper I propose an economic explanation for the reluctance to devalue and the use of trade controls, namely, the flight that can be expected to occur if the devaluation is anticipated. In an effort to avoid or offset the effects of this currency flight, countries may use direct controls. I shall analyze the properties of using import tariffs and export subsidies, with or without an anticipated devaluation, to affect the balance of payments and obtain the social optimum.'